Reconstruction of Customary Criminal Law Based on Balinese Hindu Local Wisdom - Made Gede Arthadana (Fakultas Hukum, Universitas Warmadewa, 2023)
Law is a set of rules that bind and compel society. The implementation process must be enforced by imposing sanctions so that the objectives of the law can be achieved. The purpose of the law is to provide universal benefits, namely how to create peace and tranquility in the community that can be felt concretely by all levels of society. Indonesia already has original law as a regulator of life that is born from the soul of the community which is called customary law. Customary law cannot be separated from the formation and development of national law, including criminal law. The criminal law of the Dutch colonial heritage which is not in accordance with the values of the life of the Indonesian people needs to be renewed by constructing the values of customary law so that it can apply effectively and ideally, which is known as customary criminal law because in customary law there are regulations on customary criminal law. In the legal system, especially those related to legal substance or legal products, both written and unwritten, as well as decisions from judicial institutions, can be extracted from legal sources in the form of local wisdom, especially those in Bali. One of them comes from the lontar which is then explored the values, principles and legal concepts. Regarding Law, Politics and Institutions, it is also contained in Balinese Hindu lontars which are spread in almost all corners of the region in Bali. This is important in the development and renewal of customary law and criminal law in synergy as a legal reconstruction based on Balinese Hindu local wisdom.